Resistência à dessecação e morfologia de ovos de Odonata neotropicais - Giraldin, Maíra Machado (2020)
The Odonata species are distributed along with all kinds of water bodies, being present in streams, lakes, and ponds. Many of them can be found found in fish farming ponds, which provide excellent secondary habitats for species development. However, the larvae provide economic losses to the fish farmers, and the major reason is due to immature fish predation by the Odonata larvae which habit the ponds. During the ponds transition from an activity to another, the fish farmers drain out the ponds, aiming the elimination of pathogens and among them, the Odonata larvae. After the ponds refill, it has been observed in previous studies that the Odonata eggs develop rapidly, leading us to formulate the hypothesis which the species had gone through a selective pressure, which led to the evolution of more resistant eggs to desiccation. We will then, experimentally test the effect of the desiccation in the laboratory studying two neotropical Odonata species: Micrathyria hesperis (Ris 1911) and Perithemis mooma (Kirby, 1889). The hatch efficiencies showed that both species of this study do not suffer the effect of the water absence upon the larvae hatching. This result upholds the 3 hypothesis that eggs from Odonata species in which habitat temporary water bodies exhibit adaptive traits that maximize de immature survival in ephemerous environments. The species Micrathyria hesperis and Perithemis mooma are phylogenetically distant, indicating the desiccation resistance could be distributed among the Odonata.